2023
DOI: 10.2147/jir.s386381
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory and Antioxidant Effects of Liposoluble C60 at the Cellular, Molecular, and Whole-Animal Levels

Abstract: Introduction Liposoluble carbon-60 (C60) has potential applications in many fields, including cosmetics, medical devices, and medicine, but its specific mechanism of action remains unclear. This study explored whether liposoluble C60 could be delivered to human organs, tissues, and cells through blood, extracellular fluid, and cell culture fluid and whether it exerts anti-inflammatory and antioxidant effects at the molecular, cellular, and whole-animal levels. Methods A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…ROS accumulation is considered as the principal cause of sperm motility decline during semen preservation [49]. In this regard, CF-C 60 has been shown to act as a powerful antioxidant that exerts important protective effects in cells [50][51][52]. For example, it has been reported that CF-C 60 protected the gut from the toxic effects of deoxyniurenol by reducing ROS levels and that it signi cantly improved growth performance and immune function in mice [53].…”
Section: Discussionmentioning
confidence: 99%
“…ROS accumulation is considered as the principal cause of sperm motility decline during semen preservation [49]. In this regard, CF-C 60 has been shown to act as a powerful antioxidant that exerts important protective effects in cells [50][51][52]. For example, it has been reported that CF-C 60 protected the gut from the toxic effects of deoxyniurenol by reducing ROS levels and that it signi cantly improved growth performance and immune function in mice [53].…”
Section: Discussionmentioning
confidence: 99%
“…According to biological studies, fullerene derivatives may have the following types of activity: antioxidant [ 8 , 9 , 10 ], anti-inflammatory [ 11 ], antibacterial [ 12 ], anticancer [ 10 , 13 ], antiviral [ 10 , 14 ], and others. When searching for drugs, by changing the structure of fullerene derivatives, it is possible to provide an accurate “tuning” of their structures for: obtaining a medicinal substance with a certain biological effect; or for creating means for delivering a medicinal product to the site of exposure without side effects in other tissues or organs.…”
Section: Introductionmentioning
confidence: 99%
“…Investigating the transmission pathways of fat-soluble C-60 in aqueous solutions or human bodily fluids constitutes an intriguing research avenue [29][30][31][32][33][34][35][36]. Our previous study elucidated that fat-soluble C-60 oil disperses in aqueous solutions, producing a potent antioxidant effect [5]. Fat-soluble C-60 oil exerts a more robust antioxidant effect compared to vitamin C in aqueous environments [5].…”
mentioning
confidence: 99%
“…Our previous study elucidated that fat-soluble C-60 oil disperses in aqueous solutions, producing a potent antioxidant effect [5]. Fat-soluble C-60 oil exerts a more robust antioxidant effect compared to vitamin C in aqueous environments [5]. Similarly, even a small volume of fat-soluble C-60 oil effectively inhibits the proinflammatory effects of human neutrophils in cell culture media [5].…”
mentioning
confidence: 99%
See 1 more Smart Citation